The Influence of Workload, Work Stress and Intrinsic Motivation on Work Life Balance in Working Students - Sri Harahap; Juliana Nasution; Nurul Jannah (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
The phenomenon of students working while studying, as observed at STAI Panca Budi Perdagangan, highlights the growing need for a balance between work and study. Students face challenges such as pressure to excel academically and at work, which can trigger stress and disrupt their work-life balance. This study aims to determine the effect of workload, work stress, and intrinsic motivation on the work-life balance of executive class students at STAI Panca Budi Perdagangan. The method employed is quantitative, utilising a survey approach. Data collection techniques are carried out by distributing questionnaires to 60 respondents. The data obtained are analyzed using the regression analysis method multiple linear regression with the help of statistical software. The results of the analysis indicate that workload, work stress, and intrinsic motivation have a simultaneous and positive effect on work-life balance. To some extent, the three variables also show a significant effect. It was found that financial independence is the main reason students work. Effective workload management and stress reduction, combined with high intrinsic motivation, can help students achieve a better balance between study and work, thereby improving their quality of life and performance. This study reveals the importance of workload management and strengthening intrinsic motivation to achieve a balance between work and personal life for working students.